Comparison of Physicochemical Characteristics of Starch Isolated from Sweet and Grain Sorghum. (12th July 2016) - Ahmed, Abuelgasim Mohamed; Zhang, Changquan; Liu, Qiaoquan
Abstract : The worldwide interest about sweet sorghum ( Sorghum bicolor L. Moench) goes towards stem sugar, but little has been focused on its grain. The starches were isolated from the grains of eight sweet and four grain sorghum varieties, and their physical, chemical, and morphological properties were carefully compared. The results reflected that starch from sweet varieties usually had larger granule size than that from grain ones, especially from two sweet varieties GL-4 and GL-6 with the granule size of 15.49 μ m and 15.67 μ m, respectively. The amylose content of sweet varieties starch was lower than that of grain ones. For water solubility index, starch from sweet varieties ranked top, whereas that from grain varieties ranked top for swelling power. The starch from both sweet and grain had A-type crystalline pattern, while the data from 13 C NMR reflected pattern differences forC 1 andC 6 resonance between sweet and grain varieties. Chains length distribution from sweet varieties debranched starch was found a little different from grain one. The starch particles surface of sweet sorghum was smooth with some dents, while that from grain was smooth without appearance of dents. As sweet sorghum has ability to withstand harsh environments where other crops do not and is characterized by low production cost, the extensive potential existed for starch from sweet varieties to be used in starch industries.